A Defect Detection Method for Flexible Thermal Control Film Manufacturing Process Driven by Digital Twin - LI Rongyi; TIAN Shuaiqi; DAI Mingqiu; XU Youqiang; LI Xianbin; HOU Kailin (Journal of Harbin University of Science and Technology, 2025)
The thermal radiation characteristics of flexible thermal control films are the core elements determining the accuracy of thermal balance control on the surface of spacecraft. During the coating process, dynamic fluctuations in process parameters often cause some defects. Therefore, how to monitor defects in real time has become a key issue to ensure the quality of coating. In view of the rigid constraints of traditional monolithic architecture in the defect detection of flexible films, this paper proposes a digital twin system based on microservice architecture. By decoupling system functional modules and adopting distributed service governance, high concurrency and high availability online monitoring of the film manufacturing process is achieved. Then, a vacuum coating defect detection algorithm is designed, integrating adaptive convolution + spatial pyramid module, enhancing multi-scale features through FPN/ PAN, optimizing anchor boxes and lightweight design, achieving a detection speed of 140 FPS at 91. 5% accuracy. This successfully realizes the deep integration of the digital twin system and deep learning algorithms, providing a real-time visual quality monitoring solution for the flexible film manufacturing process.